DEMOKRATISASI PASCA HOSNI MUBARAK : PETA KEKUATAN PERCATURAN POLITIK MESIR - , MACHMUD YUNUS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis aims to determine how the process of democratization of Egypt after Hosni Mubarak , particularly the strength of the political map of post- revolution Egypt . The emergence of the opposition movement with the movement of people power in Egypt is very interesting to study . As well as looking at a map win political power in the General Election held in a democratic Egypt . Repressed opposition groups during the post- revolution Egypt 's authoritarian regime into a new force in the political history of Egypt . In this ha is the Islamists , the Muslim Brotherhood and Salafi . However , the strength of the Egyptian military is still influential in the fight to Egypt after Hosni Mubarak politics . This study uses theoretical frameworks Samuel P. Huntington : The Third Wave : Democratization , to see the process of democratization Egypt after Hosni Mubarak . The collapse of the Egyptian revolution is a legitimate leader and increasing poverty . Those factors that led to the democratization of Egypt . This study concluded at least two things : ( a) The collapse of Hosni Mubarak's legitimacy is a driving factor Egyptian revolution . ( b ) The emergence of the opposition as a new force in the political history of Egypt . Namely Islamists , during the authoritarian regime banned before this group to evolve . Since it is considered dangerous to authoritarian regimes . Map of Egypt post-revolution political forces are divided into at least first , Islamists who dominate the democratic ELECTION namely the Muslim Brotherhood -affiliated Freedom and Justice Party ( Hizb al - Hurriyah wa âAdalah ) the first order and an- Salafi Nour Party ( Hizb al - Nur ) in the second . Second , the Nationalists is a stronghold of Hosni Mubarak's National Democratic Party and the third , is an independent group . Nevertheless there are still influential military force in Egypt after the government system Hosni Mubarak . Top Muslim Brotherhood is offered Shari'a . Muslim Brotherhood likely to be more moderate than the Salafi group . There are at least three challenges facing democracy in Egypt . System of authoritarian leaders , military intervention in practical politics , and the strength of the Islamists , afraid across strong ideology with Western democratic values